Causal Relationship between Asset Prices and Output in the United States: Evidence from the State-Level Panel Granger Causality Test. Issue 10 (2nd October 2016) - Emirmahmutoglu, Furkan; Balcilar, Mehmet; Apergis, Nicholas; Simo-Kengne, Beatrice D.; Chang, Tsangyao; Gupta, Rangan
Abstract : Emirmahmutoglu F., Balcilar M., Apergis N., Simo -Kengne B. D., Chang T. and Gupta R. Causal relationship between asset prices and output in the United States: evidence from the state-level panel Granger causality test, Regional Studies . This paper investigates the causal relationship between asset prices and output across US states using a bootstrap panel Granger causality approach which allows not only for heterogeneity and cross-sectional dependence to be accounted for but also interdependency between asset markets. Empirical results from a trivariate vector autoregression (VAR) comprising real house prices, real stock prices and real per capita personal income over 1975–2012 reveal the existence of a unidirectional causality running from both asset prices to output. This confirms the leading indicator property of asset prices for the real economy, while also substantiating the wealth and/or collateral transmission mechanism.